Implementasi Sekolah Balita Melalui Program Pos Pelayanan Terpadu (Posyandu) (Belajar Kasus Di Desa Gayam) - Suprapto Suprapto (Penerbit Widina, Widina Media Utama, 2022)
Posyandu now provides educational services as well as health care through toddler schools. Toddler education is a link between Posyandu BKB and Pos PAUD activities. Toddlerhood is a critical stage in human development. All human instruments are produced in this toddler age, not only intelligence but also psychological and physical skills, which is known as the golden era of development. The purpose of this research is to determine the implementation of under-five schools via the Posyandu program. It can lessen and prevent early children growth and development failures, from posyandu programs to toddler schools. As a result, cadre training is required to make early childhood more appealing in conducting the toddler school program.